Diagonalization of covariance matrix in simultaneous localization and mapping of mobile robot - Maziatun, Mohamad Mazlan; Nur Aqilah, Othman; Hamzah, Ahmad (Springer Singapore, 2019)
The purpose of this study is to analyze the behavior effects of covariance state update of different MATLAB simulation coding between modification algorithm of diaonal matrix using eigenvalue and using algorithm function of diagonalization directly, as it adds to computational cost of broadened Kalman channel based Synchronous Limitation and Mapping issue. The multiplications of the covariance matrix with other parameters will cause the increments of its dimension, which is twice the number of landmarks and result in erroneous estimation. For this inspiration an examination must be led to diminish the computational manysided quality of the covariance grid without limiting the exactness of the state estimation utilizing eigenvalue approach. The network diagonalization strategy which is connected to the covariance lattice in EKF-base SLAM must be examined due to rearrange the duplication procedure. Therefore, improvement is needed to find better iagonalization method. In view of two contextual investigations, the practices of estimation and covariance are checked.